2022
DOI: 10.1002/smi.3188
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐method exploration of mindfulness as a coping tool: Perspectives from trauma‐exposed, unhoused women residing at a drug treatment facility

Abstract: This multi-method study examined perspectives on mindfulness and coping strategies used by trauma-exposed women experiencing homelessness (WEH), residing in a state-funded residential drug treatment site in Southern California (United States). Questionnaires and in-depth focus group interviews were utilised to examine traumatic experiences over the lifespan, probable-posttraumatic stress disorder (PTSD), and coping strategies. Mindfulness was explored as a potential way to improve coping; potential benefits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…All 28 WEH had been diagnosed with an SUD as a criterion for living at the drug treatment site and had been involved with the criminal justice system; 22 (78.6%) reported an additional clinician-based diagnosed mental health condition. Nearly all women met screening criteria for probable PTSD (89%, n = 25), as presented in a related report (Garfin et al, 2023). Reports of symptoms were high: 81.48% (n = 22) reported nightmares; 92.86% (n = 26) reported avoidance symptoms; 82.14% (n = 23) felt numb/detached from others; 75% (n = 21) felt guilty or unable to stop blaming themselves or others for the events; and 85.71% (n = 24) reported been constantly on guard, watchful, or easily startled.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…All 28 WEH had been diagnosed with an SUD as a criterion for living at the drug treatment site and had been involved with the criminal justice system; 22 (78.6%) reported an additional clinician-based diagnosed mental health condition. Nearly all women met screening criteria for probable PTSD (89%, n = 25), as presented in a related report (Garfin et al, 2023). Reports of symptoms were high: 81.48% (n = 22) reported nightmares; 92.86% (n = 26) reported avoidance symptoms; 82.14% (n = 23) felt numb/detached from others; 75% (n = 21) felt guilty or unable to stop blaming themselves or others for the events; and 85.71% (n = 24) reported been constantly on guard, watchful, or easily startled.…”
Section: Resultsmentioning
confidence: 77%
“…Reports of symptoms were high: 81.48% ( n = 22) reported nightmares; 92.86% ( n = 26) reported avoidance symptoms; 82.14% ( n = 23) felt numb/detached from others; 75% ( n = 21) felt guilty or unable to stop blaming themselves or others for the events; and 85.71% ( n = 24) reported been constantly on guard, watchful, or easily startled. Additional descriptive demographic statistics are provided in a related report (Garfin et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies reported similar findings which revealed that silence helps them to know what situations and circumstances to avoid. [ 45 ] employing a problem-focused approach, [ 46 ] engaging in assertive communication, [ 47 ] preparing safety plans, [ 48 ] striving for financial independence, [ 49 ] utilizing emotional-focused techniques, [ 31 ] relying on religious/spiritual strategies, [ 50 ] practising relaxation techniques, [ 51 ] employing social coping mechanisms, [ 7 ] seeking assistance from others, [ 52 ] supporting the husband’s treatment, and accessing peer support groups. [ 53 ]…”
Section: Discussionmentioning
confidence: 99%
“…PEH report high levels of stress and elevated symptoms of anxiety (Garfin et al, 2020), depression (Garfin et al, 2020;Gutwinski et al, 2021), and PTSD (Armstrong et al, 2020;Duncan et al, 2019;Garfin et al, 2022) most likely due to exposure to cumulative traumatic life events (Buhrich et al, 2000;Edalati et al, 2017), including recurrent adverse childhood experiences (Paat et al, 2019;Sundin & Baguley, 2015), adult traumatic events (Buhrich et al, 2000;Edalati et al, 2017), and unstable housing (Karadzhov et al, 2020). Indeed findings estimate the prevalence of anxiety and depression at 40% and 48%, respectively (Garfin et al, 2020); PTSD has ranged from 19% to 79% (Ayano et al, 2020;Garfin et al, 2022;Landefeld et al, 2017). PEH also experience significant disparities in chronic physical diseases (CPD) (Brown et al, 2017;Drum, 2014;Fong, 2019), including hypertension (Salem et al, 2014), arthritis (Brown et al, 2013), and diabetes, 16% (Brown et al, 2013;Cezaretto et al, 2016;Markle-Reid et al, 2018).…”
Section: Introduction 1| Stress Among Persons Experiencing Homelessnessmentioning
confidence: 99%